Giant Right Atrial Myxoma - Jalalzai, Izatullah; Sönmez, Ebubekir; Calik, Eyupserhat; Arslan, Umit; Jalalzai, Mansoor (British Journal of Healthcare and Medical Research, 2023)
A 43-year-old female patient with no prior complaints presented to our hospital with symptoms of coughing. The doctor noticed an unexpected enlargement around right atrial area on her chest x-ray and consulted her to the cardiology department for echocardiography. The right atrium’s oval, well-circumscribed, lobulated, and mobile echogenic mass was spotted during study at the cardiology clinic and was brought to our clinic for immediate surgery. During systole and diastole, the right atrial mass moves in the direction of the tricuspid valve and gradually enters the right ventricle. It was discovered during surgery that the tumor had its origins in the right atrial free wall. Right atriotomy and mass excision were carried out while on cardiopulmonary bypass. The pathology supported the myxoma diagnosis. The patient was asymptomatic and there was no sign of a myxoma residue at post operative echocardiography.